Governança das águas em Suape: por entre território, crescimento e poder local - Gouveia, Enildo Luiz (2017)
The present research on Water Governance in Suape has paved the way for socio-environmental complexity involving water resources, since the presented reality runs through natural, socioeconomic and cultural issues. The main objective is to understand the actions of the Watershed Committees (GL 2 and Ipojuca) and the Municipal Councils (Environment and Development) in this process of Water Governance bringing a discussion on Territory, Growth and Local Power, concepts and categories that are fundamental for understanding the problem. In order to do so, we monitor these Committees and Councils during the period 2014 – 2016. We participated in various actions, meetings and, through the application of interviews with representatives of the various segments present where we could have a deeper understanding of Water Governance in Suape, identifying Weaknesses and potentialities of this process. Suape designates here the Suape Microregion composed by the municipalities of Cabo de Santo Agostinho and Ipojuca, places that in turn form the Metropolitan Region of Recife (RMR), and which play important role in the Pernambuco economy, mainly due to the installation of the Industrial Port Complex of Suape (CIPS) started in the 1970s. It is a coastal area that presents an interface with the southern forest zone of Pernambuco possessing natural and socioeconomic elements of these two geographical areas. The growth (economic, demographic, urban and industrial) in Suape, has as main engine the CIPS that, since its conception and, especially since 2007, has provoked debates on the socio-environmental impacts verified in the area, mainly with respect to the transformations especially those occurring near the mouth of the Ipojuca and Massangana rivers, with the removal and landfill of areas formerly occupied by mangroves, displacements of traditional populations, etc. This growth, coupled with the very RMR dynamics, for which Suape represents an important source of water supply, contributing with more than 50% of the water supply, increased the demand for this resource. Thus, with the increasing pressure on strategic water resources of Suape, it is necessary to understand, therefore, what role Local Government has played in Water Governance, especially on surface waters since the State of Pernambuco, in general, does not have representative groundwater reserves for water supply. The analysis of the process of Water Governance in Suape is immersed in a context of several Territories that give the theme conflictual relations. The territories of the municipalities of Cabo de Santo Agostinho and Ipojuca, the territories of the Hydrographic Basins (GL 2 and Ipojuca) and the territory of CIPS are present in the area. That is, it is a dynamic that takes place between territories. Thus, it becomes fundamental to understand such relations from the Local Power, considered here as the main element of Water Governance, in the spaces that legally were and are established, that is, the River Basin Committees and the Municipal Councils.